Eksplorasi Punokawan Dalam Perancangan Asset Game Bergaya Chibi Untuk Generasi Muda Sebagai Upaya Pelestarian Budaya Nusantara - Syaiful Anwar; Subari Subari; Saiful Yahya (LPPM STIKI Malang, 2022)
The mobile game is a game that can be played on a feature phone, a smartphone / tablet, smartwatch, and portable media players or graphing calculator. Game assets needed to develop a game. The purpose of this research to design a game asset required to play Mobile Punakawan. This study uses design method derived from the method of designing Sanyoto (2006). Design concept in this study include Thumbnail Layout, Rough Layout, and Layout Comprehensive. The final design in this study a Punakawan game assets. The data used in this research is primary data and secondary data. The primary data of the data taken from the observation results and literature review through the book Art and Character Wayang Purwa, while for secondary data such as reference books, journals existing research, and search for articles that are on the internet. Analysis of the data using the formula 5W + 1H (Who, What, When, Where, Why and How). Based on observations during the design, implementation, and testing processes conducted, it is concluded that the design assets Punakawan game includes sprite, spriteset, tileset, icons, and user interfaces that can then be used for the development of mobile games Punakawan. The character designs were used in this research is the design of a cute chibi character, as an asset to attract users of the game mulai from the age of 8 years, or who are able to operate the Smartphone. The characters used in this design include Bagong Semar, Petruk and Gareng that in the design using Corel Draw and Adobe Photoshop. Presentation Asset game design using Adobe animated CC 2018 Further research is expected to serve as a reference for developing mobile games Punakawan.